(untitled) (American Journal of Applied Statistics and Economics, 2025)
This study proposes a novel two-step sparse learning framework that combines Sparse Principal Component Regression (SPCR) with regularization methods, Lasso, Elastic Net, Ridge, and Smoothly Clipped Absolute Deviation (SCAD), to improve prediction and interpretability in high-dimensional settings. Simulation experiments were conducted under varying sample sizes, dimensionality levels, sparsity conditions, and predictor correlations to evaluate the performance of the hybrid estimators in comparison to traditional penalization approaches. Results show that SPCR-Lasso and SPCR-Enet consistently deliver superior accuracy and stability in high-dimensional, multicollinear contexts, with SPCR-Enet performing particularly well in extreme dimensionality. SPCR-SCAD demonstrated advantages in sparse, low-correlation scenarios, while Ridge regression contributed modest improvements. These findings underscore that estimator performance is strongly data-dependent and highlight the value of SPCR hybridization for mitigating multicollinearity while enhancing interpretability. The study offers practical guidance for applied researchers in fields such as genomics, finance, and climate science, and contributes methodologically by demonstrating the robustness of SPCR-based regularization in handling complex high-dimensional data structures.